Correction: A single fluorescent chemosensor for multiple targets of Cu2+, Fe2+/3+ and Al3+ in living cells and a near-perfect aqueous solution. Issue 72 (22nd September 2017) - Jo, Tae Geun; Jung, Jae Min; Han, Jiyeon; Lim, Mi Hee; Kim, Cheal
Abstract : Correction for 'A single fluorescent chemosensor for multiple targets of Cu 2+, Fe 2+/3+ and Al 3+ in living cells and a near-perfect aqueous solution' by Tae Geun Jo et al., RSC Adv., 2017, 7, 28723–28732.